Risking Ourselves in Education: Qualification, Socialization, and Subjectification Revisited - Biesta, Gert (Educational theory, 2020)
In previous publications, Gert Biesta has suggested that education should be oriented toward three domains of purpose that he calls qualification, socialization, and subjectification. Many educators, policymakers, and scholars have found this suggestion helpful. Nonetheless, the discussion about the exact nature of each domain and about their relationships to each other has been ongoing, particularly with regard to the domain of subjectification. In this article, Biesta revisits the three domains and tries to provide further clarification with regard to the idea of subjectification. He highlights that subjectification has to do with the existence of the child or student as subject of her or his own life, not as object of educational interventions. Subjectification thus has to do with the question of freedom. Biesta explains that this is not the freedom to do what one wants to do, but the freedom to act in and with the world in a “grown‐up” way.